FILOSOFI PERTUNJUKAN WAYANG PURWA - Djoko Sulaksono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
Purwa Puppet (Wayang Purwa) is one of traditional art which hasexisted for thousand years. It is internalized in man’s life. The puppetshow describes the life cycle of a man; from the first day until he died. Itis showed implicitely by the gunungan, when it is moved by the dalanguntil it is embedded for the last time (tancep kayon).